INNTEGRA: ¿Por qué integrar el valor de la Innovación Sostenible en la ciudad? - Montalván Bazán, Anthony Isaac (2019)
Indisputably, the world in which we live in is a product of an extensive historic process. In fact, the last 100 years of humanity has witnessed big dicoveries and inventions that undoubtedly revolutionized in an accelerated way our social, economical and political system. In front of it, cities have become a source and nucleus of economic and technological development. However, this system of accelerated growth and focus in the accumulation of capital has not been questioned itself if it’s impact could be sustainable in time. After the first evidence of a threatening global climate change for the survival of humanity, a series of organisms around the world have decided to undertake the decision of controlling the chaotic situation and reconstruct a new model of development. In 2015, the United Nations announced the Global Agenda until 2030 that incorporate the 17 Sustainable Development Goals and demands the transversal action from the public and private sector, university and civil society. In other words, an integrated compromise from all the sectors of society is sought. In this context, emerges the entrepreneurship INNTEGRA which seeks to join the global force and lead the local agenda by incorporating the value of Urban Sustainable Innovation.